The Effectiveness Of The SAQ And 8-PSD Exercise Methods In Increasing The Reaction Speed Of Female Futsal Goalkeepers - Fathur Rizki Amelia; Tatang Muhtar; Dinar Dinangsit (STKIP Muhammadiyah Kuningan, 2022)
The goalkeeper is the player in the last line of the futsal game and must have good reaction speed. Training methods can provide an improved reaction. Methods such as SAQ and 8-Point Star Drill are expected to increase the hand reaction of the female futsal goalkeeper. This study uses a 2x2 Factorial research design. The 2x2 factorial modifies the posttest-only control group or pretest-posttest control group design. The sample used for this study was 28 female futsal goalkeepers from Cirebon U-23 with a purposive sampling technique. The training method data shows a sig value of 0.007 for the effect of the exercise method on reaction speed. The interaction between training methods and the average reaction speed of female futsal goalkeeper U-23 Cirebon shows that the Sig value is 0.019. The comparison between 8-Point Star Drill and SAQ is above the average, with a Sig value of 0.998 and a Sig value of 0.004 for below average. So that the goalkeeper could increase the reaction speed of the female futsal goalkeeper Cirebon U23, she was able to be given SAQ and 8-point star drill.